The New Normal? - O. A. Donskikh (Moscow Polytechnic University, 2020)
The article discusses the preliminary results of the forced transition to entire online learning in the higher education system in the context of the general growth trend of the corresponding form of education in various universities around the world. The ideology defining this trend is considered. Special attention is paid to the analysis of the reality of a sharp increase in the level of control of both teachers and students by the creators of training platforms, as well as the possible consequences of this situation. It is shown that universities in different countries are seeking suitable forms of supplementing regular education with remote ones. The overall trend is a steady growth in online learning with significant variations across countries (examples include the United States, Australia, Germany, and China). It is obvious that national education systems differ significantly from each other, and with certain general trend towards online learning, each educational system is looking for its own, most suitable for the national culture, forms of education. It is also necessary to understand how online learning can be integrated into existing system without harm. At the moment, this is not clear either on the content level or methodological one. The article analyzes the temporary and long-term problems associated with the transition to distant education. The problem of technical support is probably the easiest to be solved. More serious and requiring new technologies is the problem of changing the nature of communication, which requires quite different efforts of both teachers and students if compare with the usual ones. Working on the platforms that are intended to radically change the educational environment under the slogans of ensuring an individual educational trajectory, in fact leads to the opposite. The author dwells on the problem of possible widespread replacement of conventional courses with recorded ones and, especially, the ideology of transition to online learning in the format of virtual reality, which allows the creators to exercise full control over the individual. The problem of monitoring of educational activities is discussed, which already in the current conditions makes it possible to record any actions and states of all participants in the process. The article is a reaction to the beginning of the process of widespread introduction of online technologies, and this approach, according to the author, allows to observe vividly the most painful aspects of the new situation (like the first impression of a meeting with the unknown).